2022
DOI: 10.1038/s41551-022-00922-1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of paediatric tuberculosis by optically detecting two virulence factors on extracellular vesicles in blood samples

Abstract: Sensitive and specific blood-based assays for the detection of pulmonary and extrapulmonary tuberculosis would reduce mortality associated with missed diagnoses, particularly in children. Here we report a nanoparticle-enhanced immunoassay read by dark-field microscopy that detects two Mycobacterium tuberculosis virulence factors (the glycolipid lipoarabinomannan and its carrier protein) on the surface of circulating extracellular vesicles. In a cohort study of 147 hospitalized and severely immunosuppressed chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 45 publications
0
25
0
1
Order By: Relevance
“… 130 For their part, Zheng et al identified the presence of LAM in the surface of extracellular vesicles (EVs) released from bacteria during active TB, then used conventional EV-recovery techniques to obtain concentrated samples where conventional assays were performed with great sensitivity results. 131 …”
Section: Current Advances In Nanomedicine To Exploit Mycobacterial Li...mentioning
confidence: 99%
“… 130 For their part, Zheng et al identified the presence of LAM in the surface of extracellular vesicles (EVs) released from bacteria during active TB, then used conventional EV-recovery techniques to obtain concentrated samples where conventional assays were performed with great sensitivity results. 131 …”
Section: Current Advances In Nanomedicine To Exploit Mycobacterial Li...mentioning
confidence: 99%
“…In addition, it can provide higher-resolution images, which shows potential for simple, rapid, and efficient visualization of nanomaterials. 92,93 Currently, a microimaging measurement platform for particle immunoelectrophoresis on a chip has been reported, which was built by combining microcapillary electrophoresis (μCE) with dark-field microscopy. 94,95 EVs collected from either the culture supernatant of human breast cancer cells or the blood of a mouse breast cancer model were subjected to electrophoresis experiments.…”
Section: Advances In Label-free Techniques For Sev Identificationmentioning
confidence: 99%
“…This allowed for operation via a smartphone and thus be capable of detecting tuberculosis at the point of care. 93 The development of SEV analysis techniques will undoubtedly improve the understanding of pathogen physiology and thus facilitate the development of new diagnostic and treatment methods for infections. Ulcerative Colitis (UC).…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Therefore, exosome analysis is a promising way to evaluate the health conditions from body liquid without biopsying tissues. [51][52][53] Traditional exosome biomarker analysis relies on the western blot technique, which requires laborious post-labelling processes for detection, making it impractical for rapid detection. Besides, western blot detection cannot analyze the size information of the exosomes, which is usually determined with an additional nanoparticle tracking analysis measurement.…”
Section: Exosome Analysismentioning
confidence: 99%